2019
DOI: 10.24198/jmpp.v2i2.23001
|View full text |Cite
|
Sign up to set email alerts
|

Implementasi Kebijakan Tax Allowance Dalam Upaya Peningkatan Iklim Investasi Pada Sektor Kelautan Dan Perikanan

Abstract: Sebagai Negara kepulauan dengan luas area perairan sebesar 5.8 juta km2, sektor kelautan dan perikanan Indonesia menyimpan potensi sumber daya alam yang sangat besar. Total produksi perikanan Indonesia mencapai 25 juta ton setiap tahun dan telah memberikan kontribusi terhadap Produk Domestik Bruto sebesar 6.79% pada Triwulan III Tahun 2017. Oleh karenanya sektor kelautan dan perikanan kini telah menjadi salah satu sektor yang menjadi prioritas nasional. Salah satu upaya dalam mendorong pembangunan sektor kelau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…A lot of research has been done on tax allowance. Research results (Hardianti & Setyowati, 2019) found that this tax allowance facility has not been utilized optimally in the marine and fisheries sectors. It is because the content of the policy and the context of the implementation itself can influence the implementation.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…A lot of research has been done on tax allowance. Research results (Hardianti & Setyowati, 2019) found that this tax allowance facility has not been utilized optimally in the marine and fisheries sectors. It is because the content of the policy and the context of the implementation itself can influence the implementation.…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, investment from abroad is called Foreign Investment (PMA). Ridgway and Thalib (2003) argue that investment is expected to produce multiplier effects on national economic development (Hardianti & Setyowati, 2019). It is because investment activities do not only transfer goods and capital but also transfer knowledge (Hardianti & Setyowati, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The provision of the tax allowance is also regulated in the Regulation of the Minister of Finance No.89 / PMK.010 / 2015 concerning Procedures for Providing Income Tax Facilities for Investment in Certain Business Fields and Certain Areas as well as Transfer of Assets and Sanctions for Domestic Corporate Taxpayers Provided with Income Tax Facilities. The factors that must be considered in designing the investment allowance are (Hardianti & Setyowati, 2019): 1) Eligible investment, namely that the investment allowance is applied to all forms of capital investment, or it can also be on special categories only, such as machines or equipment with advanced technology. 2) The amount of tax allowance, generally in the form of a percentage of a specific investment.…”
Section: Introductionmentioning
confidence: 99%
“…The factor that made the increase and spread of the cases high was the high rate of movement of people, transportation and employment from Bogor Regency to DKI Jakarta and vice versa (Bogor District Handbook). The government's decision to make a policy stems from the emergence of public problems that it feels necessary to find solutions (Hardianti, W. M., & Setyowati, M. S., 2019). The implementation of PSBB in Bogor Regency also has the following basis:…”
mentioning
confidence: 99%